Sexual habits of women with gynecological cancer (Research, Society and Development, 2022)
Introduction: The progression of the disease and the side effects of treatments affect the lives of patients with gynecological cancer. Pondering about sexual habits after diagnosis can make it easier to understand psychological and physical factors that influence sexuality. Objectives: To verify the sexual habits of women with gynecological cancer after diagnosis and the factors that impact the sexuality of these women. Methods: Hospitalized patients >18 years old, with gynecological cancer, answered a questionnaire with 16 closed questions, 11 about clinical profile and 5 about post-diagnosis sexual habits. Results: 83 women, 55.7±13.5 years old, participated in the study. 34.8% with staging >IIb. 77.11% declared not having an active sexual life, 36.7% being attributed to the absence of a partner, 12.05% due to pain, 16.87% due to loss of libido and 13.25% due to fear or clinical limitation. 26.51% of women report the impact of sexuality on their quality of life. Conclusion: The marital status influences the sexual function of women, but pain and loss of libido are factors that most impact the sexuality of these women. Further exploration of this theme is necessary to better instruct patients, companions and, above all, health professionals, to develop strategies focused on quality of life.